Conditional cash transfers, adult work incentives, and poverty - Skoufias, Emmanuel (Policy research working paper, 2006)
"Conditional cash transfer (CCT) programs aim to alleviate poverty through monetary and in-kind benefits, as well as reduce future levels of poverty by encouraging investments in education, health, and nutrition. The success of CCT programs at reducing poverty depends on whether, and the extent to which, cash transfers affect adult work incentives. The authors examine whether the PROGRESA program of Mexico affects adult participation in the labor market and overall adult leisure time, and they link these effects to the impact of the program on poverty. Using the experimental design of PROGRESA's evaluation sample, the authors find that the program does not have any significant effect on adult labor force participation and leisure time. Their findings on adult work incentives are reinforced further by the result that PROGRESA leads to a substantial reduction in poverty. The poverty reduction effects are stronger for the poverty gap and severity of poverty measures. "--World Bank web site